The Religious Aspect of Bertrand Russell's Philosophy - Hoernlé, R. F. Alfred (1916)
A philosophical argument is the attempt to record and communicate a vision. Or, if this phrase appears to fasten upon the philosopher the stigma of a mere visionary, let me say an intellectual perception—intellectual, because what he perceives is not even mainly made up of sense-data; perception, because it shares the directness and the self-sufficiency with which the sheer quality of sounds and sights comes to him. In speaking thus of vision or intellectual perception, I have no intention of setting up any antithesis between seeing and thinking or reasoning, nor do I mean to deny that the most comprehensive and penetrating philosophical visions are achieved, I might almost say built up, only through a toilsome process of reflection and argument. I use vision in the wide sense in which even thinking is a way of seeing, is indeed essentially the effort to see things as they are. There is no need to quote authorities, however great. My appeal is to the whole tradition which, from the earliest days of philosophy, has drawn from the eye and from its medium, the light, the language for expressing the way in which philosophical truth strikes upon the mind.